Clinical Pharmacology of Bipolar Disorder: An Updated Review of Pharmacotherapeutic Strategies - Michel Bourin (Journal of Psychology and Psychotherapy Research, 2026)
Bipolar disorder (BD) is a chronic, recurrent psychiatric illness characterized by episodes of mania, hypomania, and depression that substantially impair psychosocial functioning and quality of life. Pharmacotherapy remains the cornerstone of both acute symptom management and long-term relapse prevention. Over the past decade, advances in clinical trials and international treatment guidelines have refined the role of mood stabilizers, second-generation antipsychotics, and adjunctive therapies across different phases of illness. This review summarizes the current clinical pharmacology of bipolar disorder, emphasizing mechanisms of action, pharmacokinetic and pharmacodynamic properties, efficacy, safety, and monitoring requirements of established and emerging pharmacological treatments. Attention is given to lithium, anticonvulsant mood stabilizers, second-generation antipsychotics, the management of bipolar depression, treatment-resistant bipolar disorder, medication adherence, and individualized treatment selection. Recent evidence regarding suicide prevention, renal safety, reproductive considerations, and novel therapeutic strategies is integrated with current guideline recommendations to provide an evidence-based framework for optimizing long-term clinical outcomes.